PEMANFAATAN WOOLWICH MASSAGE TERHADAP PENGELUARAN ASI PADA IBU NIFAS - Endah Tri Wahyuni; Ratri Noviyanti (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2019)
ASI (Breast Milk) is a very important intake for babies. The WHO (World Health Organization) and UNICEF organizations recommend exclusive breastfeeding from birth until the age of 6 months so that the baby reaches optimal growth, development and health(WHO, 2016) [1]. Based on data collected by the 2014 IBFAN (International Baby Food Action Network), Indonesia ranks lowest in the 51 countries in the world that have taken part in assessing the status of policies and programs for infant and young child feeding (Infant-Young Child Feeding)(UNICEF , 2011) [2]. Coverage of exclusive breastfeeding in Indonesia is 65.16% then in DIY 76.17%. The target of achieving exclusive breastfeeding in Indonesia is 90% [3]. Sleman District Health Office said that ASI coverage in Sleman Regency reached 82.62% [4]. One effort that can be done to stimulate the hormones prolactin and oxytocin is to provide a relaxing sensation in the mother, by doing a woolwich massage that will stimulate nerve cells in the breast, passed on to the hypothalamus and responded by the anterior pituitary to secrete the prolactin hormone which will flow blood to the breast myoepithelial cells to produce breast milk. Woolwich massage is an effort to increase milk production. This research was conducted at PMB Utami Utami Ngaglik Sleman Yogyakarta. The sample of the study is postpartum mothers who do not have contra indications, postpartum mothers who breastfeed, postpartum mothers who do not have ca mamae disease. he sample consisted of 30 postpartum mothers taken by purposive sampling. The results showed that the average breastmilk expenditure before performing a woolwich massage was 85.73 with a standard deviation of 4.56322 and the average after a woolwich massage was 93.3000 with a standard deviation of 3.19644 with a sig of 0,000 <0.05. So it can be concluded that the average milk expenditure before and after doing woolwich massage is different, meaning that woolwich massage can increase the secretion and the amount of milk expenditure